Comparison of pressure resistance of double-rows and triple-rows circular stapler in rectal double stapling technique: In vitro study. Issue 28 (15th July 2022) - Mazaki, Junichi; Katsumata, Kenji; Udo, Ryutaro; Tago, Tomoya; Kasahara, Kenta; Kuwabara, Hiroshi; Enomoto, Masanobu; Ishizaki, Tetsuo; Nagakawa, Yuichi; Tsuchida, Akihiko
Abstract : Background: Anastomotic leak after gastrointestinal anastomosis is a serious complication. Anastomotic failure depends on various parameters. The aim of our study was to evaluate the pressure resistance of a new device, EEA™ circular stapler with Tri-Staple™ technology 28 mm Medium/Thick (Triple-rows circular stapler; TCS) compared with EEA™ circular stapler with DST series™ technology 28 mm, 4.8 mm staples (double-rows circular stapler; DCS). Patients and methods: We performed 30 anastomoses (DSC: 15, TCS: 15) of DST with porcine colon model in vitro. We performed following 3 comparative experiences; Experiment 1: observation of staple shape with a colonoscopy, Experiment 2: comparison of the pressure resistance, Experiment 3: comparison of leakage points. Results: There was no hypoplasia of staples and the shapes were well-formed by colonoscopy. The leakage pressure of DCS was 19.6 ± 4.4 mm Hg (mean ± standard deviation) and that of TCS was 38.6 ± 10.2 mm Hg (mean ± standard deviation). There was a significantly difference between 2 groups ( P < .001). 12 cases of DCS (80%) and 10 cases of TCS (66.7%) had leakages from Circular stapler point. 2 cases of DCS (13.3%) and 5 cases of TCS (33.3%) had leakages from Crossing points. Only 1 case of DCS had leakages from Dog ear point (6.7%). There was no significantly difference in leakage site between 2 groups ( P = .195). Conclusions: TSC showed high pressure resistance during DST compared with that of DCS. It was suggested that TCS may contribute to the reduction of anastomotic leakage rate.